2011
DOI: 10.1017/s031716710001252x
|View full text |Cite
|
Sign up to set email alerts
|

Gouty Arthropathy of the Axial Skeleton Causing Cord Compression and Myelopathy

Abstract: Can. J. Neurol. Sci. 2011; 38: 918-920 A 70-year-old Caucasian female with a past medical history of hypertension, chronic renal insufficiency, dyslipidemia, hypothyoidism, anemia, congestive heart failure, recent humeral fracture, and longstanding gout, presented with a one-year history of progressive weakness and falls, increasing "clumsiness" in her hands and weakness of the lower extremities. Bowel and bladder function were intact.On examination, resistance in the lower extremities was reduced, sensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…She presented with absence of sensory and motor function of both legs of 2 weeks’ duration. Finally, Ibrahim et al 6 reported a case of thoracic spinal cord compression at the T1–2 levels caused by gouty arthropathy in a 70-year-old woman with a 1-year history of progressive weakness in her hands and lower extremities who presented with upper motor neuron paralysis of her legs.…”
Section: Discussionmentioning
confidence: 99%
“…She presented with absence of sensory and motor function of both legs of 2 weeks’ duration. Finally, Ibrahim et al 6 reported a case of thoracic spinal cord compression at the T1–2 levels caused by gouty arthropathy in a 70-year-old woman with a 1-year history of progressive weakness in her hands and lower extremities who presented with upper motor neuron paralysis of her legs.…”
Section: Discussionmentioning
confidence: 99%
“…Published cases mainly coalesce around the progression of inflammatory back pain to catastrophic neurological involvement 6,7,8 . Although these cautionary cases of axial involvement are likely rare, there is clearly interest and concern across specialties regarding the need for carefully constructed collective investigations to elucidate the contribution of axial gouty arthropathy.…”
mentioning
confidence: 99%